Prospects of up-to-date antioxidants in the treatment of chronic eye diseases (Ukrainian Journal of Ophthalmology, 2025)
According to the World Health Organization (WHO), about 285 million people are visually impaired, and, of those, around 39 million are blind and 246 million have low vision. About 90% of the world's visually impaired people live in low-income settings while 82% of people living with blindness are aged 50 and above; this age group represents 20% of the world's population. Age-related macular degeneration (AMD), glaucoma, cataract and diabetic retinopathy are the most common causes of legal blindness and visual impairment in Ukraine, and, today, the role of free radicals in the development of these disorders is indisputable. Astaxanthin is a powerful antioxidant, more effective than lutein or zeaxanthin. Since astaxanthin has a beneficial molecular structure and multifaceted mechanism of action, is highly bioavailable and capable of crossing the blood brain barrier, it might be promising in the treatment of chronic incapacitating disorders such as glaucoma, diabetic retinopathy and AMD.
Keywords: oxidative stress; AMD; glaucoma; diabetic retinopathy; antioxidants; astaxanthin